Psychometric properties of the adapted critical language awareness instrument - Farisiyah, Umi; Istiyono, Edi; Hassan, Aminuddin; Putro, Nur Hidayanto P. S.; Ayriza, Yulia; Setiawati, Farida Agus; Mubarok, Erwin Syahril (Intelektual Pustaka Media Utama, 2025)
Concerning the Indonesian government's endeavors to safeguard Indonesia's standardized language and national language, numerous initiatives have been undertaken to uphold the disposition and consciousness of the Indonesian youth towards the language since they are the future custodians of the nation. This paper aims to present the psychometric features of the modified instrument to assess the extent of critical language awareness among undergraduate Indonesian students majoring in English. The adaptation process has six steps: translation, synthesis within the target culture, back translation, committee review, pretesting using 202 undergraduate students, and the final version of reviewers. The revised measure retains three variables: factor 1, which encompasses language variance, language prejudice, and language hegemony; factor 2, which includes bilingualism (Bil), Indonesia-English (Ind-Eng), and code-switching (CS); and factor 3, which pertains to language maintenance (LM). The customized critical language awareness measure for English students has been determined to possess both content and construct validity, establishing its validity and reliability. As mentioned earlier, this instrument can assess the level of students’ critical language awareness in English as foreign language (EFL) countries.